ANALISIS PERSEPSI, PREFERENSI, SIKAP DAN PERILAKU DOSEN FAKULTAS EKONOMI DAN BISNIS ISLAM IAIS SAMBAS TERHADAP PRODUK PERBANKAN SYARIAH - Munawir Munawir; Maskupah Maskupah (Cross-border, 2020)
The objectives of this study were 1) to determine the effect of perceptions on the attitudes of the IAIS Sambas Faculty of Economics and Business lecturers towards Islamic banking, 2) to determine the effect of preferences on the attitudes of the IAIS Sambas Faculty of Economics and Business lecturers in using Islamic banking services, 3) to knowing the effect of attitudes on the behavior of lecturers at the Faculty of Economics and Islamic Business, IAIS Sambas, towards Islamic banking This research is quantitative in nature and the data collection method in this study uses a questionnaire distribution technique. The subject uses a population of 28 respondents. The collected data were analyzed using regression analysis, which consisted of three dependent variables and one independent variable. The analysis tool used is regression analysis with the moderating variable, namely attitude, using the classical assumption method, the coefficient of determination and partial t test. Based on the analysis used, it shows that there is an effect of perception on attitudes, it is known that the significance level value of 0.049 is smaller than 0.05, which means that the hypothesis is accepted. The results also showed that there was an influence between preference for attitudes and the results of the calculations performed obtained a significance level of 0.000. This significance level is less than 0.05, which means that the hypothesis is accepted and the results of the study indicate that there is an influence between attitudes towards behavior and the calculation results obtained by a significance level of 0.000 which is smaller than 0.05, which means that the hypothesis is accepted.